The Notes of Benedict XVI on abuse by Catholic Clergy: an analysis of English and French media coverage in the international press - Gerome, Roustaveg Bibliothèque (Church, Communication and Culture, 2021)
The international press paid particular attention to Benedict XVI’s notes of 10 April 2019, on sexual abuse perpetrated by Catholic clergy. These notes are the personal thinking of the former Pope on the causes of the crisis and are entitled, ‘The Church and the scandal of sexual abuse’; their publication got the cover pages of the international press all over the world and drove criticism against the Pope Emeritus. Three news agencies, AFP, AP and Reuters, built up the narrative of the issue that was then reported by the international press, both secular and Catholic, which mostly uncritically assumed the biased reading of the issue presented. This research examines the media coverage of the issue in international English and French newspapers through a representative sample of 330 news items. The analysis focuses on the common places (topoi) and frames in the headlines/first paragraphs of news and editorial articles. Two hundred and thirty-eight of these news items (72% of those selected) did not even offer the link to the original notes. The case poses a question about the prejudices still hanging on in the mainstream newspapers about the figure of Ratzinger/Benedict XVI.